PENGARUH STRUKTUR KEPEMILIKAN SAHAM, FAKTOR EKSTERN DAN FAKTOR INTERN TERHADAP LEVERAGE DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI 2016-2018 - Dwi Agustina; Ronny Malavia Mardani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               The purpose of this study was to determine the effect of shareholding structure, external factors and internal factors on leverage and the impact on company value on mining companies listed on the stock exchange for the period 2016-2018.  The purpose of taking case studies on mining companies in this study is because in the current era globalization mining companies are one of the drivers of economic development of a country, so reserchers conduct research whether there is an influence between the structure of share ownership, external factors and internal factors as independent variables and then leverage and company velue as the dependent variable. The type of data used in this study is secondary data. The location in this study is a mining company listed on the indonesia stock exchange in the period 2016-2018. In this study the authors took a sampel using purposive sampling technique. In this study the population taken was 45 mining companies listed on the indonesia stock exchange for the period 2016-2018 and obtained a sampel of 27 companies so that the research data was 81 companies. The analysis technique used is multiple regression and direct and indirect influences.                              The results in this study case study on mining companies listed on the Indonesia Stock Exchange for the 2016-2018 period can be concluded, namely: variable ownership structure (X1), external factors (X2), internal factors (X3) does not have a significant effect on the leverage  variabel. While the structure of share ownership (X1), external factors (X2) does not have a significant effect on the firm value variabel and internal factors (X3) has a significant effect on the firm value variabel, then leverage variable (Y1) has a significant effect on the firm value variabelmemiliki ( Y2). Keyword: Stock Ownership Structure, External Factors, Internal Factors, Leverage, Company Value.